Iodine-PPh3-mediated C3-sulfenylation of indoles with sodium sulfinates - Praewpan Katrun (2018)
3-(Alkylsulfanyl)- and 3-(arylsulfanyl)indoles were efficiently prepared by the reaction of indoles with sodium sulfinates mediated by iodine-PPh3in ethanol. The salient features of the present protocol are simplicity, high efficiency, non-anhydrous conditions, environmentally friendly reagents and solvent, and short reaction time. © 2014 the Partner Organisations.